KEPUASAN MAHASISWA PRODI D.IV KEBIDANAN POLTEKKES KEMENKES PADANG DALAM MENGGUNAKAN VILEP POLTEKKES KEMENKES SEBAGAI SARANA PENDUKUNG PERKULIAHAN - Alsri Windra Doni (Jurnal Sehat Mandiri, 2021)
Vilep is an information technology learning media used in lectures at the Ministry of Health Polytechnic. Vilep was developed by the Head of PPSDM Ministry of Health of the Republic of Indonesia since 2016 through a learning social network. The problem with using Vilep is that D.IV Midwifery Study Program students in Padang have actively used Vilep, but have not used it optimally. The aim of the study was to determine the satisfaction of D.IV Midwifery Study Program students in Padang in using the Vilep Poltekkes of the Ministry of Health as a means of supporting lectures. This type of research is quantitative descriptive to determine the value of an independent variable, either one variable or more (independent) without making comparisons, or connecting with another variable. The number of respondents is 109 students. Data collection uses a questionnaire. Data analysis with univariate to describe the characteristics of each variable. The results showed that for the variable ease of use Vilep chose to agree 68 people (62,4%), for viewing as many as 85 people (78%), for ease of downloading material as many as 55 people (50.4%), for available information as many as 59 people (54.1%). Conclusion, the achievement of student satisfaction in using Vilep as a means of supporting lectures. It is hoped that all lecturers will use Vilep as a support for lectures so that students can optimally use Vilep.